2010
DOI: 10.1007/s12663-010-0040-9
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and distal Facial nerve exploration during superficial parotidectomy

Abstract: One of the most technique sensitive surgeries in the maxillofacial region is the parotid gland surgery owing to the close relation between the gland and the extra-cranial course of facial nerve. Facial nerve is generally located by means of a proximal surgical identification technique aimed at identifying the facial nerve at its point of exit from the stylomastoid foramen to its entry into the posteromedial surface of parotid gland. There are reports in the literature on distal nerve identification techniques,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Of 53 full-text studies reviewed for potential inclusion; only 10 met the inclusion criteria and were assessed for reliability ( Table 1 ). The other 43 articles were excluded with reasons (8 studies included malignant tumors[ 12 , 34 40 ], 1 study included only one patient in RFND group[ 41 ], 1 study included revision parotidectomy[ 42 ], 1 included recurrent tumors[ 43 ] ( Table 3 , Fig 1 ), 32 studies reported either AFND or RFND technique.…”
Section: Resultsmentioning
confidence: 99%
“…Of 53 full-text studies reviewed for potential inclusion; only 10 met the inclusion criteria and were assessed for reliability ( Table 1 ). The other 43 articles were excluded with reasons (8 studies included malignant tumors[ 12 , 34 40 ], 1 study included only one patient in RFND group[ 41 ], 1 study included revision parotidectomy[ 42 ], 1 included recurrent tumors[ 43 ] ( Table 3 , Fig 1 ), 32 studies reported either AFND or RFND technique.…”
Section: Resultsmentioning
confidence: 99%
“…Sharma et al recommended the use of buccal branch of facial nerve to locate the main trunk. The reason behind was due to the regular course and adequate size of this branch of facial nerve in its peripheral area co-located with stenson's duct, which enabled it to be easily identified during surgery [11]. Pia et al [12] used orbicular branch, on account of difficulty in locating the main trunk of the nerve in 5 cases of retrograde exploration of the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…So because of the little space between the mastoid process and the cancerous parotid gland, working on this are aisextremely difficult 7 . Another example of the importance of afull identification off acial nerve is in parotid gland surgery, in which the parotidgl and iscloseto the extra-cranial region of the facialnerve 8 . generally in any parotidsurgery, the identification of the facial nerve trunk is a need.…”
Section: Introductionmentioning
confidence: 99%